THE PREVALENCE OF CONSANGUINEOUS MARRIAGES AND AFFECTING FACTORS IN TURKEY: A NATIONAL SURVEY. Issue 5 (19th February 2016) - Kaplan, Sena; Pinar, Gul; Kaplan, Bekir; Aslantekin, Filiz; Karabulut, Erdem; Ayar, Banu; Dilmen, Ugur
Summary: This study was carried out by the Turkish Republic Ministry of Health to determine the prevalence of consanguineous marriage and its correlates with socio-demographic and obstetric risk factors in women in Turkey. The cross-sectional, national-level study was carried out from October to December 2013. The study population was composed of women between the ages of 15 and 65 years living in Turkey. The sample size was calculated as 9290 houses within Turkey's 81 provinces so as to improve the Turkish rural–urban expectations by means of systematic stack sampling according to the Turkish Statistical Institute's address-based vital statistics system. The target sample size was 6364, but only eligible 4913 women, who had been married, were included in the study. The consanguineous marriage frequency in the sample was found to be 18.5%, and of these 57.8% were first cousin marriages. Women living in an extended family and whose education level and first marriage ages were low, and whose perceived economic status was poor, had higher frequencies of consanguineous marriage ( p <0.001). Consanguineous marriage frequencies were higher ( p <0.001) for women who had spontaneous abortions and stillbirths or who had given birth to infants with a congenital abnormality. In this context, it is important to develop national policies and strategies to prevent consanguineous marriages in Turkey.